Targeted Genomic Profiling of Female Adnexal Tumors of Probable Wolffian Origin (FATWO). (November 2019) - Mirkovic, Jelena; Dong, Fei; Sholl, Lynette M.; Garcia, Elizabeth; Lindeman, Neal; MacConaill, Laura; Crum, Christopher P.; Nucci, Marisa R.; McCluggage, W. Glenn; Howitt, Brooke E.
Abstract : Female adnexal tumor of probable Wolffian origin (FATWO) is a rare gynecologic neoplasm of low-malignant potential presumed to be derived from mesonephric remnants in the upper female genital tract. Similarly, mesonephric remnants in the lower female genital tract are thought to be the origin for mesonephric carcinoma. Although the molecular alterations in mesonephric carcinoma have been recently reported, the pathogenesis of and molecular alterations in FATWO are not well understood. The aims of this study were to examine the molecular alterations in FATWO and to establish whether these neoplasms are molecularly similar to mesonephric carcinoma. Eight FATWOs underwent massively parallel sequencing to detect single nucleotide variations, copy number variations, and structural variants by surveying exonic DNA sequences of 300 cancer genes and 113 introns across 35 genes. Good quality DNA was isolated from 7 of 8 cases. Novel KMT2D variants (1 frameshift, 3 missense) were identified in 4 of 7 cases (57%), but were variants of uncertain biologic significance. STK11 mutations (both frameshift) were identified in 2 of 7 cases (29%); one of these was in a patient with a known history of Peutz-Jeghers syndrome. A mutation in the chromatin remodeling gene ARID1B was identified in 1 of 7 cases (14%). No cases harbored KRAS, NRAS, TP53, PIK3CA, PTEN, or DICER1 mutations. There were relatively low numbers of copy number variations, and no recurrent copy number variations were identified. One case demonstrated moderate copy gain of CCND1 . No structural variants were identified. In summary, FATWO is characterized molecularly by the absence of KRAS/NRAS mutations (characteristic of mesonephric carcinoma), absence of DICER1 mutations (characteristic of Sertoli-Leydig cell tumor) and frequent KMT2D mutations of unknown biologic significance. FATWOs exhibit a limited number of molecular aberrations that are significantly different from those reported in tumors in the differential diagnosis, and our results question the relationship of mesonephric carcinoma with FATWO. Disease-defining molecular alterations for FATWO have yet to be discovered. Abstract : Supplemental Digital Content is available in the text.